Development of a paper-based microfluidic device for the quantification of ammonia in industrial wastewater - Nonhlazeko Loveday Nxumalo; Lawrence Mzukisi Madikizela; Hendrik Gert Kruger; Stanley Chibuzor Onwubu; Phumlane Selby Mdluli (Water SA, 2020)
Ammonia is a toxic pollutant increasingly found in urban and industrial wastewater and unprotected surface water. Industry discharges and fertilizer run-off release ammonia into sewers and streams, overloading wastewater treatment plants and causing fish deaths in surface water such as rivers, sea and lakes. The purpose of this study was to develop and evaluate the effectiveness of the microfluidic paper-based device (µPAD) for the quantification of ammonia in wastewater. The µPAD fabricated had an oval-shaped pattern which was designed using CorelDraw software. The hydrophilic zones were created by printing a chromatographic paper with a Xerox wax printer (Xerox colorqube 8570). The modified version of the colorimetric method using Nessler reagent was combined with microfluidic technologies to create a low-cost monitoring system for detection of ammonia in wastewater. The method allows for ammonia determination in the range of 0–5 ppm (mg/L) with a limit of detection of 3.34 ppm. This study indicated that a µPAD was successfully used to quantify the concentration of ammonia in wastewater.